IMPLEMENTASI PELAYANAN PROGRAM KELUARGA HARAPAN (PKH) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Abd. Rohman; Retno Ayu Dewi Novitawati (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2020)
The purpose of this study was to determine the implementation of PKH services in an effort to improve people's welfare. This study used a qualitative approach with data analysis techniques using Miles and Huberman's theory, namely data reduction, presentation and conclusion. The results showed that the implementation of PKH in Batu City was done according to established policy procedures, starting from the initial data collection process by officers / assistants to the distribution and utilization process. The process of providing PKH funds is carried out by PKH facilitators according to the data that has been submitted and validated, along with maximum assistance. The process of withdrawing PKH funds, participants can take their own through the Automatic Teller Machine (ATM) which has been facilitated by the Hope Family Program Implementation Unit (UPPKH) after receiving information on disbursement from sub-district facilitators. The implementation of PKH services is well with done for the support of various parties, especially the assistant coordinator and sub-district assistant. Meanwhile, what has been an obstacle so far is the awareness of the community to attend regular meetings, either socialization or assistance for the community independence program of PKH recipients. In this case, the Government is considered necessary to also mobilize public support in general so that PKH will receive broad support as an effort to improve community welfare.